Key Factors Driving the Adoption Internet of Things in Manufacturing Industry and Associated Challenges (International Journal of Food and Nutritional Sciences, 2022)
The Internet of Things (IoT) is an innovative technology that is rapidly gaining popularity. It has a wide range of uses in daily life as well as in many other sectors and industries. A worldwide dynamic information network with linked items and devices that strives to connect and interact with other people, services, and devices at any time and from anywhere is what might be referred to as this phenomenon. In order to build intelligence into devices so they can process information and data and learn, the Internet of Things (IoT) makes use of a variety of cutting-edge technologies. As a result, real-time, autonomous, and intelligent decision-making systems are created that mimic human decision-making processes and eliminate the need for human involvement and intervention. In this paper, the author discusses the key drivers involved in the adoption of IoT in manufacturing industry. In addition to that, author also discussed the possible associated challenges such as security and cost that are preventing from harnessing the full potential of IoT which need attention for future exploration.